Insulin-induced lypodistrophy in hemodialyzed patients: A new challenge for nephrologists?. Issue 6 (November 2019) - Gentile, S.; Strollo, F.; Satta, E.; Della-Corte, T.; Romano, C.; Guarino, G.
Abstract: Diabetes Mellitus (DM) is the most common cause of renal failure and ESRD all over the world, and often requires an individualized insulin treatment regimen. Malnutrition, depression-related eating behavior changes, high on-off-dialysis day-to-day glycemic variability and frequent hypoglycemic events occurring during or immediately after dialysis make it hard to identify best insulin dosage in hemodialyzed patients. This suggests a prudent attitude including non-stringent control, despite which repeated hypoglycemia quite often occurs in such patients. When looking for possible sources of hypoglycemia, health professionals too often overlook the identification of skin lipodystrophy (LD) due to an incorrect insulin injection technique. This mini-review focuses on the high frequency (57%) of LD in a cohort of 1004 insulin-treated people with DM on dialysis consecutively referring to our joint medical centers, and on its relationship with hypoglycemia and glycemic control/variability. When taking on such patients, care team members accept to face a complex disease burdened with several risk factors requiring high professional skills, and have to keep in mind also the possible presence of any LD areas eventually interfering with expected results. A timely educational intervention on the correct injection technique can help reduce the high risk of hypoglycemia and large glycemic variability in dialysed people with DM.